Platelet Activation by Extracellular Matrix Proteins in Haemostasis and Thrombosis - Watson, Steve P. (Current Pharmaceutical Design, 2009)
The prevention of excessive blood loss to avoid fatal haemorrhage is a pivotal process for all organisms possessing a circulatory system. Increased circulating blood volume and pressure, as required in larger animals, make this process all the more important and challenging. It is essential to have a powerful and rapid system to detect damage and generate an effective seal, and which is also exquisitely regulated to prevent unwanted, excessive or systemic activation so as to avoid blockage of vessels. Thus, a highly specialised and efficient haemostatic system has evolved that consists of cellular (platelets) and protein (coagulation factors) components. Importantly, this is able to support haemostasis in both the low shear environment of the venous system and the high shear environment of the arterial system. Endothelial cells, lining the entire circulation system, play a crucial role in the delicate balance between activation and inhibition of the haemostatic system. An intact and healthy endothelium supports blood flow by preventing attachment of cells and proteins which is required for initiation of coagulation and platelet activation. Endothelial cells produce and release the two powerful soluble inhibitors of platelet activation, nitric oxide and prostacyclin, and express high levels of CD39 which rapidly metabolises the major platelet feedback agonist, ADP. This antithrombotic environment however can rapidly change following activation or removal of endothelial cells through injury or rupture of atherosclerotic plaques. Loss of endothelial cells exposes the subendothelial extracellular matrix which creates strong signals for activation of the haemostatic system including powerful platelet adhesion and activation. Quantitative and qualitative changes in the composition of the subendothelial extracellular matrix influence these prothrombotic characteristics with life threatening thrombotic and bleeding complications, as illustrated by formation of atherosclerotic plaques or the disorder Ehler-Danlos syndrome, which is caused by a defect in collagen synthesis and is associated with fragile blood vessels. This review will focus on the role of the subendothelial matrix in haemostasis and thrombosis, highlighting its potential as a target for novel antithrombotics.